POTENSI TERAPEUTIK Punica granatum SEBAGAI ANTIOKSIDAN ALAMI PADA STRES OKSIDATIF YANG DIINDUKSI PLASMA PREEKLAMPSI - Januarsih, Januarsih (Bajang Institute, 2025)
Preeclampsia is a complication of pregnancy characterised by hypertension and endothelial dysfunction, with oxidative stress as one of its main mechanisms. An imbalance between reactive oxygen species (ROS) and the antioxidant system leads to endothelial cell damage that contributes to disease progression. The main biomarkers of oxidative stress include increased malondialdehyde (MDA) and decreased superoxide dismutase (SOD) activity. Assess the therapeutic potential of Punica granatum extract as a natural antioxidant against oxidative stress in HUVECs endothelial cells exposed to preeclamptic plasma. An in vitro experimental study was conducted using HUVECs cultures divided into five groups: negative control, preeclamptic control, and three treatment groups with 25, 50, and 100 µg/mL doses of Punica granatum extract. Parameters measured were MDA levels and SOD activity. Statistical analysis used one-way ANOVA with Tukey's post hoc test (p<0.05). Exposure to preeclamptic plasma increased MDA levels and decreased SOD activity significantly. Treatment with Punica granatum extract reduced MDA levels and increased SOD activity significantly, especially at a dose of 50 µg/mL which was close to normal control values. Punica granatum extract showed therapeutic potential as a natural antioxidant in reducing oxidative stress due to preeclampsia in HUVECs. This study supports the development of Punica granatum as a phytotherapy candidate in antioxidant-based management of preeclampsia